Virus isolation from calves with respiratory tract disease - Feridun Öztürk; Sibel Yavru; Atilla Şimşek (Eurasian Journal of Veterinary Sciences)
Blood samples were collected intotubes with EDTA from 15 calves with a respiratory disease and inoculated on to foetal calf kidney (FCK) cell culture. Two viruses isolated from these blood samples. The cytophatic effect (CPE) in FCK cell culture were occurred fourth and fifth passage.